The Leadership of Sultanah Nukila and Gender Politics in The Sixteenth-Century Sultanate of Ternate - Fatma Fatma; Irfan Ahmad; Aswati Aswati; Willem Christiaan Manuhutu; Muhammad Rusydan Hi Arby (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This article examines Sultanah Nukila's leadership within the political structure of the Sultanate of Ternate during the sixteenth century, positioning gender relations as an important element in the dynamics of power within the maritime sultanates of Maluku. The background of the study concerns the dynastic succession crisis following the death of Sultan Bayanullah, the increasing Portuguese intervention in the spice trade, and the political and religious pressures that threatened the sultanate's stability. The main research problem concerns how female leadership gained political legitimacy in this crisis. The novelty of this research lies in the integration of gender historical analysis with the local political structure of Ternate through the examination of dynastic genealogy, customary relations involving bobato and soa, and the political philosophy of jou se ngofa ngare as a framework of political legitimacy. The issue is examined through a critical reading of Portuguese colonial sources, modern historiography, and Ternate oral traditions to understand the relationship among power, political culture, and gender within the sultanate. The study employs the historical method, including heuristic inquiry, source criticism, interpretation, and historiography, with gender as the principal analytical approach. The findings demonstrate that Nukila’s leadership functioned effectively in maintaining dynastic continuity, managing political elites, constructing local legitimacy, and responding to Portuguese colonial pressures, thereby playing an important role in maintaining the political stability of the Sultanate of Ternate during the early modern period.